A Qualitative Study of the Views of Patients With Medically Unexplained Symptoms on The BodyMind Approach®: Employing Embodied Methods and Arts Practices for Self-Management - Payne, Helen; Brooks, Susan Deanie Margaret (Frontiers in Psychology, 2020)
The arts provide openings for symbolic expression by engaging the sensory experience in the body they become a source of insight through embodied cognition and emotion, enabling meaning-making, and acting as a catalyst for change. This synthesis of sensation and enactive, embodied expression through movement and the arts is capitalised on in The BodyMind Approach® (TBMA). It is integral to this biopsychosocial, innovative, unique intervention for people suffering medically unexplained symptoms (MUS) applied in primary healthcare. The relevance of embodiment and arts practices in TBMA are discussed in relation to the views of participants in the pursuit of self-management. If widely employed TBMA could have as an enormous impact, reach and significance for patients and global health services. This original pre-clinical trial qualitative research reports on the perceptions of participant patients with generic MUS, a world-wide issue usually treated by either psychological or physiotherapy. TBMA is not a therapy but a health education programme founded upon the concept of an integration of psychological with physiological, bodily, sensory experiences. Thematic analysis of qualitative data sets from open-ended questions in semi-structured interviews and a written questionnaire post intervention is presented. Five aspects which appear to be key to learning self-management were derived from analysing the data: 1) body with mind connections; 2) importance of facilitation; 3) potential benefits; 4) preparedness for change; 5) self-acceptance/compassion. This article advances the discourse on the nature of self-management for MUS through changing the mind-set and the relationship participants have with their bodily symptom/s through employing embodied methods and arts practices, challenging current, and solely verbal, psychological conceptual frameworks. Rigor lies in the method of data analysis using cross verification of credibility between reported findings and scrutiny by stakeholders. We conclude that facilitated TBMA groups employing embodied methods and arts practices can act as a method for developing the self-management of MUS and improving wellbeing.